Evolution of Public Health Expenditure Financed by the Romanian Social Health Insurance Scheme From 1999 to 2019 - Radu, Ciprian-Paul; Pana, Bogdan Cristian; Pele, Daniel Traian; Costea, Radu Virgil (Frontiers in Public Health, 2021)
The Romanian health system is financed mainly through the following: Social Health Insurance - 82%, State Budget - 18%, and since 2006, Local Authorities (up to an additional 8%). The shares of the types of expenditure reflect the importance of each sector in the overall health system, and trends in expenditure show the impact of financing on the health sector’s structural changes. We analysed the 20-year trend of the Social Health Insurance budget, from 1999 to 2019. The influences of the different allocations, subcategories, and new budget categories appearing over time were adjusted to reveal relevant trends. Of the 14 medical service categories and the stand-alone Administrative expenditure category, six expenditure categories including Hospital services, Total drugs, and Primary care showed stationary 20-year trends; five including Medical devices, Dialysis, and Homecare services showed ascendant trends; and four including Dentistry and Emergency services showed descendant trends. Stationary trends imply no structural changes in the health sector of relevant magnitude to impact the financing shares of major categories: hospitals, drugs, or primary care. Emerging trends related to the impact of different reforms were revealed only in the low share of expenditures categories. The allocation methodology and statistical analysis of the trends reveal a new perspective on the evolution of health sector in Romania.